2002
DOI: 10.1053/bbmt.2002.v8.pm12434947
|View full text |Cite
|
Sign up to set email alerts
|

CD25+ immunoregulatory T-cells of donor origin suppress alloreactivity after BMT

Abstract: We have previously identified donor-derived Thy1+ alphabeta T-cell receptor (TCR)+ CD4+ CD8- regulatory T-cells that suppress GVH reactivity induced by donor leukocyte infusion (DLI) after BMT. These cells develop in the recipient thymus and may play a role in the maintenance of donor-host tolerance after allogeneic BMT. In the present study, we sought to further characterize the T-cells responsible for the regulatory cell activity in our model. Lethally irradiated recipient AKR mice (H-2k) received transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 28 publications
5
58
1
Order By: Relevance
“…Although we were unable to detect regulatory activity using in vitro assays where individual cell populations were employed at ratios present in the spleens of MC, we did observe a failure of nylon wool-passaged SC preparations from DLI recipients to induce severe GVHD in secondary, irradiated allogeneic recipients and demonstrated that T cells present within MC before DLI were predominantly responsible for this effect. Although we have not defined the specific T cell subset(s) responsible for suppression in this model, these data are consistent with the finding that postthymic, donor-derived CD25 ϩ T cells developing within allogeneic chimeras are important for restricting the development of GVHD (28,29). Nevertheless, it is important to note that even in the face of this regulatory impedance, sufficient activation, proliferation, and effector CTL differentiation occur to permit significant lymphohematopoietic GVH reactivity and antitumor responses in MC.…”
Section: Discussionsupporting
confidence: 82%
“…Although we were unable to detect regulatory activity using in vitro assays where individual cell populations were employed at ratios present in the spleens of MC, we did observe a failure of nylon wool-passaged SC preparations from DLI recipients to induce severe GVHD in secondary, irradiated allogeneic recipients and demonstrated that T cells present within MC before DLI were predominantly responsible for this effect. Although we have not defined the specific T cell subset(s) responsible for suppression in this model, these data are consistent with the finding that postthymic, donor-derived CD25 ϩ T cells developing within allogeneic chimeras are important for restricting the development of GVHD (28,29). Nevertheless, it is important to note that even in the face of this regulatory impedance, sufficient activation, proliferation, and effector CTL differentiation occur to permit significant lymphohematopoietic GVH reactivity and antitumor responses in MC.…”
Section: Discussionsupporting
confidence: 82%
“…[20][21][22][23]32 Indeed, it has been shown that CD4 ϩ CD25 ϩ T cells lower the incidence, and even completely suppress the development, of GVHD after major histocompatibility complex (MHC)-mismatched or even haploidentical murine SCT. [20][21][22][23]33 Importantly, the ratio of CD4 ϩ CD25 ϩ T cells to other cells in the donor graft has been shown to be predictive of GVHD risk. 21 The suppressor phenotype of CD4 ϩ CD25 ϩ T reg cells has also been shown to be preserved after ex vivo expansion and subsequent infusion into SCT recipients, providing a potential rationale for similar strategies in human SCT.…”
Section: Discussionmentioning
confidence: 99%
“…20 Other murine studies have confirmed that infusing donor-derived CD4 ϩ CD25 ϩ T cells may suppress the development of GVHD in a dose-dependent fashion after allogeneic SCT. [21][22][23] These results have led many to propose that enrichment, expansion, or both of CD4 ϩ CD25 ϩ T cells in donor grafts might similarly decrease the incidence of GVHD after SCT in humans, though this has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…93 These findings have been confirmed in animal models, which have shown that donor-derived CD4 þ CD25 þ immunoregulatory T cells are educated in the host thymus and induce tolerance with a concomitant reduction in GVHD. 94,95 The role of T reg infusions as DLI remains to be determined.…”
Section: Future Directionsmentioning
confidence: 99%